Interaction of tactile input in the human primary and secondary somatosensory cortex: a magnetoencephalographic study - Hoechstetter, Karsten; Rupp, André; Stančák, Andrej; Meinck, Hans-Michael; Stippich, Christoph; Berg, Patrick; Scherg, Michael (NeuroImage, 2001)
Interaction of simultaneous tactile input at two finger sites in primary (SI) and secondary somatosensory cortex (SII) was studied by whole-head magnetoencephalography. Short pressure pulses were delivered to fingers of the right and left hand at an interstimulus interval of 1.6 s. The first phalanx of the left digit 1 and four other sites were stimulated either separately or simultaneously. We compared four sites with increasing distance: the second phalanx of left digit 1, left digit 5, and digits 1 and 5 of the right hand. The temporal evolution of source activity in the contralateral SI and bilateral SII was calculated using spatiotemporal source analysis. Interaction was assessed by comparing the source activity during simultaneous stimulation with the sum of the source activities elicited by separate stimulation. Significant suppressive interaction was observed in contralateral SI only for stimuli at the same hand, decreasing with distance. In SII, all digits of the same and the opposite hand interacted significantly with left digit 1. When stimulating bilaterally, SII source waveforms closely resembled the time course of the response to separate stimulation of the opposite hand. Thus, in bilateral simultaneous stimulation, the contralateral input arriving first in SII appeared to inhibit the later ipsilateral input. Similarly, the separate response to input at two unilateral finger sites which arrived slightly earlier in SII dominated the simultaneous response. Our results confirm previous findings of considerable overlap in the cortical hand representation in SII and illustrate hemispheric specialization to contralateral input when simultaneous stimuli occur bilaterally.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 04.03.2021